A Novel Irrigation System in Percutaneous Renal Surgery - Hosseini, Mohammad Mehdi; Afrasiabi, Mohammad Amin; Negahdari, Eskandar; Aminsharifi, Alireza; Shakeri, Saeed; Tadayon, Alireza; Ahmad, Ejaz; Manaheji, Farhad (Urology Journal, 2013)